USE OF STANDARD MULTIPLE REGRESSION TO UNDERSTAND AND PREDICT DELIVERY OF SECURE LAND RIGHTS IN SELECTED WESTERN DISTRICTS OF UGANDA - Mugisha David Begumya,; Dr. Mucunguzi Abel, (IJRDO - Journal of Business Management, 2020)
According to Oxfam secure land rights and equitable land governance are vital in achieving poverty eradication, sustainable land use, reduced land conflict and social stability (Oxfam, 2018). The study used a quantitative sample of 394 obtained from a target population of 2116 respondents involved in land policy implementation. This study used standard multiple regression to determine the central-local governmental relations variables that have the strongest unique contribution in explaining current land policy implementation. This study also used standard multiple regression to determine the central-local governmental relations variables that have the strongest unique contribution in predicting land policy implementation in selected western districts of Uganda.